Transcriptional signatures of wheat inforescence development - VanGessel, Carl (2022)
In order to maintain global food security, it will be necessary to increase yields of the cereal crops that provide most of the calories and protein for the world’s population, which includes common wheat (Triticum aestivum L.). An important wheat yield component is the number of grain-holding spikelets which form on the spike during inflorescence development. Characterizing the gene regulatory networks controlling the timing and rate of inflorescence development will facilitate the selection of natural and induced gene variants that contribute to increased spikelet number and yield. In the current study, co-expression and gene regulatory networks were assembled from a temporal wheat spike transcriptome dataset, revealing the dynamic expression profiles associated with the progression from vegetative meristem to terminal spikelet formation. Consensus co-expression networks revealed enrichment of several transcription factor families at specific developmental stages including the sequential activation of different classes of MIKC-MADS box genes. This gene regulatory network highlighted interactions among a small number of regulatory hub genes active during terminal spikelet formation. Finally, the CLAVATA and WUSCHEL gene families were investigated, revealing potential roles for TtCLE13, TtWOX2, and TtWOX7 in wheat meristem development. The hypotheses generated from these datasets and networks further our understanding of wheat inflorescence development. Introduction